Spatial relationships between soil attributes and corn yield in no-tillage system - Rodrigues, Marcos Sales [UNESP]; Cora, Jose Eduardo [UNESP]; Fernandes, Carolina [UNESP] (Sociedade Brasileira de Ciência do Solo, 2012)
Soil properties play an important role in spatial variability of crop yield. However, a low spatial correlation has generally been observed between maps of crop yield and of soil properties. The objectives of the present investigation were to assess the spatial pattern variability of soil properties and of corn yield at the same sampling intensity, and evaluate its cause-and-effect relationships. The experimental site was structured in a grid of 100 referenced points, spaced at 10 m intervals along four parallel 250 m long rows spaced 4.5 m apart. Thus, points formed a rectangle containing four columns and 25 rows. Therefore, each sampling cell encompassed an area of 45 m(2) and consisted of five 10 m long crop rows, in which the referenced points represented the center. Samples were taken from the layers 0-0.1 m and 0.1-0.2 m. Soil physical and chemical properties were evaluated. Statistical analyses consisted of data description and geostatistics. The spatial dependence of corn yield and soil properties was confirmed. The hypothesis of this study was confirmed, i.e., when sampling the soil to determine the values of soil characteristics at similar to sampling intensity as for crop yield assessments, correlations between the spatial distribution of soil characteristics and crop yield were observed. The spatial distribution pattern of soil properties explained 65 % of the spatial distribution pattern of corn yield. The spatial distribution pattern of clay content and percentage of soil base saturation explained most of the spatial distribution pattern of corn yield.

Atributos do solo desempenham papel importante na variabilidade espacial da produtividade da cultura. Entretanto, o que se observa, geralmente, é uma baixa correlação espacial entre mapas de produtividade e mapas de atributos do solo. O objetivo deste trabalho foi estudar o padrão de distribuição espacial dos atributos do solo e da produtividade de milho e sua relação de causa e efeito, quando avaliados em semelhante intensidade amostral. Foi utilizada uma malha amostral de 100 pontos referenciados na área experimental. Os pontos foram espaçados em intervalos regulares de 10 m ao longo de quatro transeções de 250 m, espaçadas em 4,5 m. Os pontos formaram um retângulo com quatro colunas e 25 linhas. Portanto, cada célula amostral foi composta de cinco linhas da cultura com 10 m, totalizando uma área de 45 m2 cada, onde o ponto referenciado foi considerado o centro da célula. As amostras foram coletadas nas profundidades de 0-0,1 e 0,1-0,2 m. Foram avaliados atributos físicos e químicos do solo. Realizou-se a análise estatística descritiva dos dados e geoestatística. A produtividade de milho e os atributos do solo apresentaram dependência espacial. A hipótese deste estudo foi confirmada: quando a intensidade amostral dos atributos do solo é semelhante àquela da produtividade da cultura, é observada correlação entre os padrões de distribuição espacial de atributos do solo e produtividade da cultura. Os padrões de distribuição espacial dos atributos do solo explicaram 65 % do padrão de distribuição espacial da produtividade do milho. Os padrões de distribuição espacial dos teores de argila e da porcentagem de saturação por bases foram os que melhor explicaram o padrão de distribuição espacial da produtividade do milho.
Relação espacial entre atributos do solo e produtividade de milho em sistema de semeadura direta
Keywords: Geostatistics; Precision agriculture; soil sampling intensity; spatial correlation; Zea mays